The Central American Indigenous Ethnic Groups Knowledge Center Project: A Synopsis - Rojas Morales, Nydia (2006)
This document contains an overview of the activities and achievements of the project "Knowledge Center / Central American Indigenous Ethnic Groups" in the School of Library, Documentation and Information, National University, Costa Rica, as part of strategies to implantation in indigenous communities, information services that contribute to their development.